The rise and fall of the Aztec empire - Stoltman, Joan (World history (Lucent Press), 2018)
Describes the culture, lifestyle, art, weapons, and religion of the Aztec people and their eventual destruction at the hands of Spanish invaders. Includes color illustrations, sidebars, notes on the text, a timeline, sources for further information, and an index.